2022
DOI: 10.3390/jcdd9030085
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Single Bout of Resistance Exercise with Blood Flow Restriction on Arterial Stiffness in Older People with Slow Gait Speed: A Pilot Randomized Study

Abstract: Purpose: Low-intensity resistance exercise with moderate blood-flow restriction (LIRE-BFR) is a new trending form of exercises worldwide. The purpose of this study was to compare the acute effect of a single bout of traditional resistance exercise (TRE) and LIRE-BFR on arterial stiffness in older people with slow gait speeds. Methods: This was a randomized, controlled clinical study. Seventeen older adults (3 men; 14 women; 82 ± 5 years old) completed a session of TRE (n = 7) or LIRE-BFR (n = 10). At baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Studies analyzing six parameters of vascular stiffness were identified: the augmentation index (AI), corrected AI (AI75), Systemic Vascular Resistance (SVR), Pulse Wave Analysis (PWV), Large-Artery Elasticity Index (LAEI), and Small-Artery Elasticity Index (SAEI). In the case of AI, AI75, SVR, LAEI, and SAEI data were not sufficient to perform calculations: AI: Four studies were identified [ 43 , 44 , 45 , 46 ], but only Amorim et al showed a more decisive influence of BFR over non-BFR exercise [ 43 ]. AI75: None of the three identified studies reported any significance in the change in AI75 between BFR and non-BFR exercise [ 28 , 43 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies analyzing six parameters of vascular stiffness were identified: the augmentation index (AI), corrected AI (AI75), Systemic Vascular Resistance (SVR), Pulse Wave Analysis (PWV), Large-Artery Elasticity Index (LAEI), and Small-Artery Elasticity Index (SAEI). In the case of AI, AI75, SVR, LAEI, and SAEI data were not sufficient to perform calculations: AI: Four studies were identified [ 43 , 44 , 45 , 46 ], but only Amorim et al showed a more decisive influence of BFR over non-BFR exercise [ 43 ]. AI75: None of the three identified studies reported any significance in the change in AI75 between BFR and non-BFR exercise [ 28 , 43 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of AI, AI75, SVR, LAEI, and SAEI data were not sufficient to perform calculations: AI: Four studies were identified [ 43 , 44 , 45 , 46 ], but only Amorim et al showed a more decisive influence of BFR over non-BFR exercise [ 43 ]. AI75: None of the three identified studies reported any significance in the change in AI75 between BFR and non-BFR exercise [ 28 , 43 , 45 ]. SVR: According to Karabulut et al, BFR exercise is more effective for decreasing SVR than low-intensity non-BFR exercise but less effective compared to high-intensity non-BFR training [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations